Halogen-free flame-retardant TPU (thermoplastic polyurethane) sheath material for charging pile as well as preparation method and application thereof

The method of combining TPU modified with magnesium hydroxide micropowder by POSS nanoparticles solves the problem of flammability of TPU materials, significantly improves flame retardant performance and thermal stability, and is suitable for high-demand occasions such as liquid-cooled charging pile cables.

CN119899518APending Publication Date: 2025-04-29宁波聚泰新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411920228.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing TPU materials are flammable and have insufficient flame retardant performance, which limits their application in high demand occasions, especially in liquid-cooled charging pile cables, the materials need to have excellent flame retardant performance and thermal management capabilities.

Method used

The TPU modified with POSS nanoparticles is combined with magnesium hydroxide micropowder as a composite flame retardant. Through the synergistic effect of the modified POSS nanoparticles and magnesium hydroxide micropowder, the flame retardancy and thermal stability of the TPU material are significantly improved.

Benefits of technology

It realizes the efficient flame retardant performance and thermal stability of TPU materials, reduces fire risk, and is suitable for high-temperature and high-pressure environments of liquid-cooled charging pile cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899518A_ABST
    Figure CN119899518A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of TPU (thermoplastic polyurethane) materials, and relates to a halogen-free flame-retardant TPU sheath material for a charging pile as well as a preparation method and application of the halogen-free flame-retardant TPU sheath material. The TPU sheath material is prepared from the following raw materials in parts by weight: 60-80 parts of TPU, 3-30 parts of a composite flame retardant, 0.5-3 parts of a lubricant, 0.5-3 parts of an antioxidant and 1-5 parts of an auxiliary agent, the composite flame retardant is obtained by compounding TPU (thermoplastic polyurethane) modified by POSS (polyhedral oligomeric silsesquioxane) nano particles and magnesium hydroxide micro powder. The POSS-based flame retardant containing phosphorus, nitrogen and silicon elements is synthesized and can play a synergistic role to improve the flame retardance; tPU modified by POSS nano particles and magnesium hydroxide micro powder are compounded to serve as a composite flame retardant, and the proportion of the TPU to the magnesium hydroxide micro powder is strictly regulated and controlled, so that the thermal stability of the material is improved; in addition, the raw material ratio of the system is optimized, the mechanical property of the TPU sheath material is ensured, and the overall flame retardant property of the material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of TPU materials and relates to a halogen-free flame-retardant TPU sheath material for a charging pile and a preparation method and application thereof. Background Art

[0002] In the research and application of thermoplastic polyurethane (TPU) materials, halogen-free flame retardant technology has become an important development trend. TPU is widely used in many industries such as footwear, cables, automotive interiors and medical devices due to its excellent physical properties such as wear resistance, flexibility, tear resistance and chemical resistance. However, a significant disadvantage of ordinary TPU materials is its low oxygen index (LOI), which means that it is a flammable material and will produce droplets during combustion, which not only increases the risk of fire, but also limits the use of TPU in occasions with strict requirements for flame retardancy.

[0003] In order to improve the flame retardant properties of TPU, researchers in this field usually add halogen-free flame retardants to the TPU matrix. This type of flame retardant not only improves the flame retardancy of TPU, but also avoids the problem of halogen-containing flame retardants releasing harmful gases during combustion, which meets the requirements of environmental protection and health.

[0004] With the rapid development of the new energy vehicle industry and the acceleration of charging infrastructure construction, higher requirements are placed on the performance of charging pile cables. In the case of high-power fast charging, traditional charging pile cables are prone to overheating due to the heat generated by the current passing through, which not only poses a safety hazard but may also shorten the service life of the cable. In order to overcome this problem, liquid cooling technology has been introduced into the design of charging pile cables due to its excellent thermal management capabilities, effectively solving the problem of cable temperature rise during high-power charging.

[0005] Despite this, the design and manufacture of liquid-cooled charging pile cables still face many challenges, including appropriate material selection, complex structural design, and cost control. Therefore, in order to meet the needs of these special applications, it is urgent to develop a halogen-free flame-retardant TPU sheath material that has excellent flame retardant properties and meets the requirements of liquid cooling systems. This new material must not only be able to effectively prevent the occurrence of fires, but also ensure the stability and durability of the cable under long-term operation, while reducing costs as much as possible, so that liquid-cooled charging pile cables can be more economical and feasible in practical applications. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides a halogen-free flame-retardant TPU sheath material for a charging pile, and a preparation method and application thereof.

[0007] One object of the present invention is achieved by the following technical solutions:

[0008] A halogen-free flame-retardant TPU sheath material for a charging pile. The raw materials for preparing the TPU sheath material include the following components in parts by weight: 60 to 80 parts of TPU, 3 to 30 parts of a composite flame retardant, 0.5 to 3 parts of a lubricant, 0.5 to 3 parts of an antioxidant, and 1 to 5 parts of an auxiliary agent.

[0009] The composite flame retardant is obtained by compounding TPU modified by POSS nanoparticles and magnesium hydroxide micropowder;

[0010] The structural formula of the POSS nanoparticle-modified TPU is shown in Formula I:

[0011]

[0012] The structure of R1 in Formula I is shown in Formula II:

[0013]

[0014] The structure of R2 in Formula II is shown in Formula III:

[0015]

[0016] The structure of R3 in Formula III is shown in Formula IV:

[0017]

[0018] Preferably, the compounding ratio of the TPU modified by POSS nanoparticles and the magnesium hydroxide powder in the composite flame retardant is 1:(0.5-2).

[0019] The present invention introduces TPU modified by POSS nanoparticles into the composite flame retardant of TPU material, which can give it better compatibility in TPU; at the same time, the inorganic core of POSS nanoparticles can improve the thermal stability of the material; POSS nanoparticles are obtained by modification of 6-chloro-1,3,5-triazine and DOPO, and contain three flame retardant components of phosphorus, nitrogen and silicon in the molecular structure, and have both condensed phase and gas phase flame retardant effects. In addition, magnesium hydroxide micropowder can generate fire-resistant magnesium oxide when thermally decomposed, which covers the surface of the material and blocks further combustion of the material, and can also release bound water, absorb a large amount of heat, and reduce the temperature of the surface of the TPU sheath material, and the water vapor generated by the bound water can also be used as a smoke suppressant; therefore, the composite use of TPU modified by POSS nanoparticles and magnesium hydroxide micropowder can make the two produce a synergistic effect during combustion, greatly improving the flame retardancy of the TPU material.

[0020] Preferably, in the TPU modified by POSS nanoparticles, the preparation method of POSS nanoparticles comprises the following steps:

[0021] S1, mixing the first solvent and the acid at 50-70° C. for 10-60 min, then adding 3-aminopropyltriethoxysilane (APTES), stirring and condensing and reflux at 60-95° C. for 10-20 h to obtain OA-POSS;

[0022] S2, adding 6-chloro-1,3,5-triazine and DOPO to the second solvent and the modified cross-linking agent, condensing and reflux at 50-80° C. for 8-24 hours to obtain an intermediate phosphorus-containing compound;

[0023] S3. Add OA-POSS and the intermediate phosphorus-containing compound into a third solvent and a sodium bicarbonate solution, place in an ice bath at 0-5° C. for 2-8 hours, and wash and dry to obtain modified POSS nanoparticles.

[0024] In the method for preparing POSS nanoparticles, preferably, the first solvent includes one or more of methanol, toluene and acetonitrile.

[0025] In the method for preparing POSS nanoparticles, the acid preferably includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid and acetic acid, and more preferably hydrochloric acid.

[0026] In the method for preparing POSS nanoparticles, preferably, the mass ratio of the first solvent to the acid is 10:(1-3).

[0027] In the method for preparing POSS nanoparticles, preferably, the mass ratio of 3-aminopropyltriethoxysilane to acid is 3:(0.5-3).

[0028] In the method for preparing POSS nanoparticles, preferably, the mass ratio of 6-chloro-1,3,5-triazine to DOPO is 1.5:(2-8).

[0029] In the method for preparing POSS nanoparticles, preferably, the second solvent is ethanol.

[0030] In the method for preparing POSS nanoparticles, preferably, the modified cross-linking agent includes aldehyde compounds and / or isocyanate compounds.

[0031] Preferably, the aldehyde compound can be one or more of formaldehyde, paraformaldehyde, acetaldehyde, and valeraldehyde; the isocyanate compound can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.

[0032] More preferably, the modified cross-linking agent is paraformaldehyde.

[0033] In the method for preparing POSS nanoparticles, preferably, the third solvent includes one or more of chloroform, dichloromethane, tetrahydrofuran, cyclohexane, N,N-dimethylformamide, and ethyl acetate.

[0034] In the method for preparing POSS nanoparticles, preferably, the ratio of OA-POSS, the intermediate phosphorus-containing compound and the third solvent is (10-20) g: (16-50) g: (25-75) mL.

[0035] Preferably, the preparation method of the composite flame retardant comprises the following steps:

[0036] S1. Under the protection of nitrogen atmosphere, polytetrahydrofuran was dissolved in acetone, stirred evenly, and then the catalyst dibutyltin dilaurate was added and heated, and diphenylmethane diisocyanate was slowly added, and refluxed for 3-5h, and POSS nanoparticles were added, and the reaction was continued for 1-2h before stopping heating;

[0037] S2, the solution obtained in S1 is allowed to stand at room temperature until there are no bubbles, then slowly poured into a polytetrafluoroethylene mold, and allowed to stand at room temperature for 1 to 2 days to obtain POSS nanoparticle-modified TPU;

[0038] S3, compounding the TPU modified by POSS nanoparticles and magnesium hydroxide micropowder and performing extrusion granulation to obtain a composite flame retardant masterbatch, which is then tableted using an automatic tablet press to obtain a composite flame retardant.

[0039] POSS (Polyhedral Oligomeric Silsesquioxanes) nanoparticles are a unique class of inorganic-organic hybrid materials, which are composed of a three-dimensional cage structure composed of a siloxane (Si-O-Si) skeleton. Since APTES contains triethoxysilane groups and amino groups, the present invention obtains OA-POSS containing amino groups by hydrolyzing APTES for subsequent modification. The present invention further modifies DOPO with 6-chloro-1,3,5-triazine. DOPO can form a carbon layer during the combustion process, which can not only inhibit the spread of flames, but also reduce the generation of smoke and toxic gases. The introduction of 6-chloro-1,3,5-triazine can decompose at high temperatures to release non-combustible gases, which can play a role in diluting oxygen, or undergo endothermic decomposition to take away heat and reduce the combustion surface temperature. Introducing it into the POSS structure can significantly improve the flame retardant properties of the composite material. In addition, the introduction of modified DOPO can improve the dispersibility of POSS nanoparticles in the polymer matrix. The modified POSS nanoparticles can be better compatible with the polymer matrix and enhance the bonding force between the interfaces, thereby improving the overall performance of the composite material.

[0040] In the preparation method of the composite flame retardant, preferably, the mass ratio of polytetrahydrofuran to acetone is 1:(2-8).

[0041] In the preparation method of the composite flame retardant, preferably, the mass ratio of isophorone diisocyanate to POSS nanoparticles is 1:(10-30).

[0042] In the preparation method of the composite flame retardant, preferably, the compounding ratio of the TPU modified by POSS nanoparticles and the magnesium hydroxide powder is 1:(0.5-2).

[0043] Preferably, the particle size of the POSS nanoparticles is 50 to 500 nm.

[0044] Preferably, the particle size of the magnesium hydroxide powder is 0.1 to 100 μm.

[0045] Preferably, the lubricant includes one or more of polyethylene wax, calcium stearate, barium stearate, paraffin wax and zinc stearate.

[0046] Preferably, the antioxidant includes one or more of antioxidant 1010, antioxidant 1098, antioxidant 168, antioxidant 1076, antioxidant 1790, antioxidant 245, and antioxidant 246.

[0047] Preferably, the auxiliary agent includes a light stabilizer and / or a crosslinking agent.

[0048] Preferably, the light stabilizer includes one or more of o-hydroxybenzophenone, benzotriazole, salicylate, triazine, and substituted acrylonitrile. It is used to improve the weather resistance and light stability of the material and prevent aging and performance degradation caused by ultraviolet radiation. The light stabilizer protects the material by absorbing or reflecting ultraviolet rays, quenching excited molecules, capturing free radicals, etc.

[0049] Preferably, the crosslinking agent includes one or more of di-tert-butyl peroxide (DBHP), diisopropylbenzene peroxide (DCP) and vinyltriethoxysilane (A1522), which are used to promote chemical bonding between polymer chains and improve the mechanical properties, heat resistance and chemical resistance of the material.

[0050] The second object of the present invention is achieved by the following technical solutions:

[0051] A method for preparing a halogen-free flame-retardant TPU sheath material for a charging pile, the preparation method comprising the following steps: mixing raw materials evenly and then extruding and granulating them to obtain the halogen-free flame-retardant TPU sheath material for the charging pile.

[0052] The third object of the present invention is achieved by the following technical solutions:

[0053] A halogen-free flame-retardant TPU sheath material for a charging pile is used in preparing a liquid-cooled TPU charging pile cable sheath.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] 1. The present invention synthesizes a POSS-based flame retardant containing phosphorus, nitrogen and silicon elements, wherein the phosphorus-containing component can simultaneously exert gas-phase and condensed-phase flame retardant effects, the nitrogen component can generate nitrogen-carbon compounds with high thermal stability during combustion, and the silicon-containing component helps the substrate to generate a ceramic stable carbon layer during combustion, and synergistically exerts a condensed-phase flame retardant effect with the phosphorus-containing component, thereby protecting the substrate from external flame burning and reducing the fire hazard.

[0056] 2. In the halogen-free flame-retardant TPU sheath material for charging piles provided by the present invention, TPU modified by POSS nanoparticles and magnesium hydroxide micropowder are compounded as a composite flame retardant, and the addition amounts of the two are strictly controlled to achieve a significant improvement in the flame retardant properties and thermal stability of the TPU sheath material.

[0057] 3. In the halogen-free flame-retardant TPU sheath material for charging piles provided by the present invention, POSS nanoparticles are modified and then used to modify TPU, so that after the TPU modified by POSS nanoparticles and magnesium hydroxide micropowder are compounded, the POSS nanoparticles will be evenly distributed around the magnesium hydroxide micropowder, greatly improving the compatibility between the flame retardant and the TPU matrix.

[0058] 4. In the halogen-free flame-retardant TPU sheath material for charging piles provided by the present invention, by adjusting the raw material ratio in the material system, a synergistic effect is produced between the prepared raw materials, and the flame retardant properties of the whole material can be significantly improved while ensuring the mechanical properties of the TPU sheath material. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The TPU raw material and magnesium hydroxide powder of Example 1.

[0060] In the figure: a, TPU raw material; b, magnesium hydroxide powder;

[0061] Figure 2 It is the TPU modified by POSS nanoparticles in Example 1 and the composite flame retardant sheet after extrusion granulation and tableting.

[0062] In the figure: a, TPU modified by POSS nanoparticles; b, composite flame retardant sheet after extrusion granulation and tableting;

[0063] Figure 3 This is a vertically burned 4 mm specimen prepared in Example 1.

[0064] In the figure: a, before combustion; b, after combustion. DETAILED DESCRIPTION

[0065] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not used to limit the scope of the present invention. And the drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0066] Example 1

[0067] The raw materials for preparing the halogen-free flame-retardant TPU sheath material for the charging pile in this embodiment include the following components by weight: 77 parts of TPU, 15 parts of composite flame retardant (the compounding ratio of TPU modified by POSS nanoparticles and magnesium hydroxide powder is 1:0.5, 10 parts of TPU modified by POSS nanoparticles, 5 parts of magnesium hydroxide powder), 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0068] The preparation method of POSS nanoparticles in the present embodiment comprises the following steps:

[0069] S1. Mix 150 mL MeOH and 15 mL HCl (1 M) in a three-necked flask at 60° C. for 30 min, then slowly add 5 g APTES, and stir and reflux at 90° C. for 16 h to obtain OA-POSS, as shown in reaction formula I:

[0070]

[0071] S2. Add 2.12 g of 6-chloro-1,3,5-triazine and 10.8 g of DOPO into a flask containing 80 mL of ethanol and 1.2 g of paraformaldehyde, condense and reflux at 55° C. for 12 h, wash and dry to obtain an intermediate phosphorus-containing compound, as shown in reaction formula II:

[0072]

[0073] S3, 10.95g OA-POSS and 16.32g intermediate phosphorus-containing compound were added to 100ml tetrahydrofuran and 10ml sodium bicarbonate solution, and ice-bathed at 0-5°C for 4h, and then washed and dried to obtain modified POSS nanoparticles, as shown in reaction formula III:

[0074]

[0075] The preparation method of the composite flame retardant in this embodiment comprises the following steps:

[0076] (1) Under nitrogen atmosphere, 7.992 g of polytetrahydrofuran (M = 2000 g / mol) was dissolved in 50 ml of acetone, stirred evenly, 0.01 g of dibutyltin dilaurate was added and heated, 1 g of diphenylmethane diisocyanate was slowly added, refluxed for 3 to 5 h, 25 g of POSS nanoparticles was added, and the reaction was continued for 1 to 2 h before stopping heating, as shown in Reaction Formula IV;

[0077]

[0078] (2) allowing the solution obtained in (1) to stand at room temperature until there are no bubbles, then slowly pouring it into a polytetrafluoroethylene mold, and allowing it to stand at room temperature for 1 day to obtain POSS nanoparticle-modified TPU;

[0079] (3) The POSS nanoparticle-modified TPU and magnesium hydroxide powder are compounded and extruded and granulated to obtain a composite flame retardant masterbatch, which is then tableted using an automatic tablet press to obtain a composite flame retardant.

[0080] The preparation of the halogen-free flame-retardant TPU sheath material for the charging pile in this embodiment includes the following steps: the raw materials are mixed evenly and then extruded and granulated to obtain the halogen-free flame-retardant TPU sheath material for the charging pile.

[0081] Figure 1 The TPU raw material and magnesium hydroxide powder of Example 1. In the figure: a, TPU raw material; b, magnesium hydroxide powder;

[0082] Figure 2 The TPU modified by POSS nanoparticles and the composite flame retardant after extrusion granulation and tableting of Example 1. In the figure: a, TPU modified by POSS nanoparticles; b, composite flame retardant after extrusion granulation and tableting.

[0083] Example 2

[0084] The difference between this embodiment and embodiment 1 is that the compounding ratio of POSS nanoparticle-modified TPU and magnesium hydroxide powder in the composite flame retardant is 1:1, and the specific preparation raw materials include the following components by weight: 77 parts of TPU, 15 parts of composite flame retardant (7.5 parts of TPU modified by POSS nanoparticles, 7.5 parts of magnesium hydroxide powder), 3 parts of calcium stearate, 10983 parts of antioxidant, 1 part of 2-(2'-hydroxy-5'-methylphenyl) benzotriazole (UV-326), and 1 part of di-tert-butyl peroxide (DBHP).

[0085] The rest is the same as in Example 1.

[0086] Example 3

[0087] The difference between this embodiment and embodiment 1 is that the compounding ratio of POSS nanoparticle-modified TPU and magnesium hydroxide powder in the composite flame retardant is 1:2, and the specific preparation raw materials include the following components in parts by weight: 77 parts of TPU, 15 parts of composite flame retardant (5 parts of TPU modified by POSS nanoparticles, 10 parts of magnesium hydroxide powder), 3 parts of zinc stearate, 1683 parts of antioxidant, 1 part of 2-ethylhexyl salicylate, and 1 part of vinyl triethoxy silane (A1522).

[0088] The rest is the same as in Example 1.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 1 is that the raw materials for preparing the TPU sheath material include the following components in parts by weight: 84.5 parts of TPU, 7.5 parts of composite flame retardant (the compounding ratio of TPU modified by POSS nanoparticles and magnesium hydroxide powder is 1:0.5, 5 parts of TPU modified by POSS nanoparticles, 2.5 parts of magnesium hydroxide powder), 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0091] The rest is the same as in Example 1.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 1 is that the raw materials for preparing the TPU sheath material include the following components in parts by weight: 69.5 parts of TPU, 22.5 parts of composite flame retardant (the compounding ratio of TPU modified by POSS nanoparticles and magnesium hydroxide powder is 1:0.5, 15 parts of TPU modified by POSS nanoparticles, 7.5 parts of magnesium hydroxide powder), 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0094] The rest is the same as in Example 1.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 1 is that the raw materials for preparing the TPU sheath material include the following components in parts by weight: 59 parts of TPU, 33 parts of composite flame retardant (the compounding ratio of TPU modified by POSS nanoparticles and magnesium hydroxide powder is 1:0.5, 22 parts of TPU modified by POSS nanoparticles, 11 parts of magnesium hydroxide powder), 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0097] The rest is the same as in Example 1.

[0098] Comparative Example 4

[0099] The difference between this comparative example and Example 1 is that only TPU modified with POSS nanoparticles is used as the flame retardant, and the rest is the same as Example 1.

[0100] The specific raw materials for the preparation include the following components by weight: 77 parts of TPU, 15 parts of TPU modified with POSS nanoparticles, 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0101] Comparative Example 5

[0102] The difference between this comparative example and Example 1 is that only magnesium hydroxide powder is used as the flame retardant, and the rest is the same as Example 1.

[0103] The specific raw materials for the preparation include the following components by weight: 77 parts of TPU, 15 parts of magnesium hydroxide powder, 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0104] Comparative Example 6

[0105] The difference between this comparative example and Example 1 is that unmodified POSS nanoparticles and magnesium hydroxide micropowder are compounded as the composite flame retardant, and the rest is the same as Example 1.

[0106] The specific preparation raw materials include the following components by weight: 77 parts of TPU, 15 parts of composite flame retardant (the compounding ratio of POSS nanoparticles and magnesium hydroxide powder is 1:0.5, 10 parts of POSS nanoparticles, 5 parts of magnesium hydroxide powder), 3 parts of polyethylene wax, 10103 parts of antioxidant, 1 part of 2-hydroxy-4-methoxybenzophenone (UV-057), and 1 part of diisopropylbenzene peroxide (DCP).

[0107] The preparation method of POSS nanoparticles in this comparative example comprises the following steps: 150 mL MeOH and 15 mL HCl are mixed in a three-necked flask at 60° C. for 30 min, 5 g APTES is slowly added, and the mixture is stirred, condensed and refluxed at 90° C. for 16 h to obtain POSS nanoparticles.

[0108] Comparative Example 7

[0109] The only difference between this comparative example and Example 1 is that no composite flame retardant is added.

[0110] The raw materials of the above-mentioned embodiment and comparative example were mixed evenly and then extruded and granulated to obtain TPU sheath material. Then, relevant mechanical properties and flame retardant properties were tested. The specific test results are shown in Figure 3 and Table 1.

[0111] Table 1 Performance test data of TPU sheath materials in embodiments and comparative examples

[0112]

[0113]

[0114] Figure 3 This is a comparison chart of the results of the TPU sheath material of Example 1 in the vertical burning test v.

[0115] In the figure, a is before combustion; b is after combustion.

[0116] like Figure 3 As shown in Table 1, it can be seen from Examples 1 to 3 that the TPU sheath material prepared using the raw materials and proportions within the scope of the technical solution of the present invention has excellent flame retardant properties and mechanical properties. Since the modified POSS nanoparticles are introduced into the TPU segment, it has better compatibility with TPU; at the same time, the inorganic core of POSS can improve the thermal stability of the material; in addition, magnesium hydroxide powder can generate fire-resistant magnesium oxide when it is thermally decomposed, covering the surface of the material to prevent further combustion of the material, and at the same time, it can also release bound water, absorb a large amount of heat, and reduce the temperature of the surface of the TPU sheath material, and the water vapor generated by the bound water can also be used as a smoke suppressant; therefore, the present invention uses TPU modified by POSS nanoparticles and magnesium hydroxide powder for compound use, which can produce a synergistic effect between the two during combustion, and can greatly improve the flame retardancy and mechanical properties of the TPU sheath material.

[0117] It can be seen from Comparative Examples 1 to 3 that in Comparative Example 1, when the proportion of TPU in the system is too high, although the mechanical properties are good, the flame retardant properties are very poor and cannot reach a qualified flame retardant level; in Comparative Examples 2 to 3, when the proportion of the composite flame retardant is too high, although the flame retardant properties are excellent, the mechanical properties of the material are greatly reduced.

[0118] It can be seen from Comparative Examples 4 to 6 that when the flame retardant is not compounded and the POSS nanoparticles are not modified, the flame retardant properties and mechanical properties of the prepared TPU sheath material are significantly reduced.

[0119] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0120] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0121] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A halogen-free flame-retardant TPU sheath material for a charging pile, characterized in that: The raw materials for preparing the TPU sheath material include the following components by weight: 60-80 parts of TPU, 3-30 parts of composite flame retardant, 0.5-3 parts of lubricant, 0.5-3 parts of antioxidant and 1-5 parts of auxiliary agent; The composite flame retardant is obtained by compounding TPU modified by POSS nanoparticles and magnesium hydroxide micropowder; The structural formula of the POSS nanoparticle-modified TPU is shown in Formula I: The structure of R1 in Formula I is shown in Formula II: The structure of R2 in Formula II is shown in Formula III: The structure of R3 in Formula III is shown in Formula IV:

2. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 1, characterized in that: The compounding ratio of the modified POSS nanoparticles to the magnesium hydroxide micropowder in the composite flame retardant is 1:(0.5-2).

3. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 1, characterized in that: In the TPU modified by the POSS nanoparticles, the preparation method of the POSS nanoparticles comprises the following steps: S1, mixing the first solvent and the acid at 50-70° C. for 10-60 min, then adding 3-aminopropyltriethoxysilane (APTES), stirring and condensing and reflux at 60-95° C. for 10-20 h to obtain OA-POSS; S2, adding 6-chloro-1,3,5-triazine and DOPO to the second solvent and the modified cross-linking agent, condensing and reflux at 50-80° C. for 8-24 hours to obtain an intermediate phosphorus-containing compound; S3. Add OA-POSS and the intermediate phosphorus-containing compound into a third solvent and a sodium bicarbonate solution, place in an ice bath at 0-5° C. for 2-8 hours, and wash and dry to obtain modified POSS nanoparticles.

4. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 3, characterized in that: The first solvent includes one or more of methanol, toluene and acetonitrile; and / or, the acid comprises one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, and acetic acid; and / or, the mass ratio of the first solvent to the acid is 10:(1-3); And / or, the mass ratio of 3-aminopropyltriethoxysilane to acid is 3:(0.5-3); and / or, the mass ratio of 6-chloro-1,3,5-triazine to DOPO is 1.5:(2-8); And / or, the second solvent is ethanol; and / or, the modified cross-linking agent comprises an aldehyde compound and / or an isocyanate compound; and / or, the third solvent comprises one or more of chloroform, dichloromethane, tetrahydrofuran, cyclohexane, N,N-dimethylformamide, and ethyl acetate; And / or, the ratio of the OA-POSS, the intermediate phosphorus-containing compound and the third solvent is (10-20) g: (16-50) g: (25-75) mL.

5. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: (1) Under the protection of nitrogen atmosphere, polytetrahydrofuran is dissolved in acetone, stirred evenly, a catalyst dibutyltin dilaurate is added and heated, diphenylmethane diisocyanate is slowly added, refluxed for 3 to 5 hours, POSS nanoparticles are added, the reaction is continued for 1 to 2 hours, and then heating is stopped; (2) allowing the solution obtained in (1) to stand at room temperature until there are no bubbles, then slowly pouring it into a polytetrafluoroethylene mold, and allowing it to stand at room temperature for 1 to 2 days to obtain POSS nanoparticle-modified TPU; (3) Compounding the POSS nanoparticle-modified TPU and magnesium hydroxide micropowder and subjecting them to extrusion granulation to obtain a composite flame retardant masterbatch, which is then tableted using an automatic tablet press to obtain a composite flame retardant.

6. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 5, characterized in that: The mass ratio of the polytetrahydrofuran to acetone is 1:(2-8); And / or, the mass ratio of isophorone diisocyanate to POSS nanoparticles is 1:(10-30); And / or, the compounding ratio of the POSS nanoparticle-modified TPU and magnesium hydroxide micropowder is 1:(0.5-2).

7. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 1, characterized in that: The particle size of the POSS nanoparticles is 50-500 nm; the particle size of the magnesium hydroxide micropowder is 0.1-100 μm.

8. The halogen-free flame-retardant TPU sheath material for a charging pile according to claim 1, characterized in that: The lubricant includes one or more of polyethylene wax, calcium stearate, barium stearate, paraffin wax, and zinc stearate; And / or, the antioxidant includes one or more of antioxidant 1010 , antioxidant 1098 , antioxidant 168 , antioxidant 1076 , antioxidant 1790 , antioxidant 245 , and antioxidant 246 .

9. A method for preparing a halogen-free flame-retardant TPU sheath material for a charging pile as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: mixing the raw materials uniformly and then extruding and granulating them to obtain a halogen-free flame-retardant TPU sheath material for a charging pile.

10. Use of a halogen-free flame-retardant TPU sheath material for a charging pile as claimed in any one of claims 1 to 8 in preparing a liquid-cooled TPU charging pile cable sheath.